PENGARUH RISIKO KREDIT, RISIKO LIKUIDITAS, DAN RISIKO OPERASIONAL TERHADAP PROFITABILITAS BANK UMUM PERSERO PERIODE 2013-2020 - Sri Wellis Anggraeni; Gusganda Suria Manda (Progress: Jurnal Pendidikan, Akuntansi dan Keuangan, 2022)
This study aims to determine the effect of credit risk, liquidity risk and operational risk either partially or simultaneously on the profitability of state-owned commercial banks listed on the IDX for the period 2013-2020. The type of research method is associative. The samples used were 4 banking companies including PT Bank Rakyat Indonesia (Persero) Tbk, PT Bank Mandiri (Persero) Tbk, PT Bank Negara Indonesia (Persero) Tbk and PT Bank Tabungan Negara (Persero) Tbk. In this study, a sampling technique was used in the form of saturated sampling with secondary data in the form of the annual financial statements of state-owned commercial banks for the period 2013-2020 which were obtained through the official website of the Indonesia Stock Exchange www.idx.co.id. The analysis technique was carried out through multiple linear regression analysis and with SPPS 16 software as data processing. This study obtained the results that credit risk and liquidity risk partially have no significant effect on profitability, while operational risk partially has a negative and significant effect on profitability. Simultaneous results, namely credit risk, liquidity risk and operational risk have a significant effect on profitability.